Knowledge of blood transfusion practices among medical students and residents - Roula A. Farah; Aida Mitri; Hiba El Rahi; Hind Al Humaidan; M. Hasan Rajab; Sabri Kemahli (Asian Journal of Transfusion Science)
A study was conducted to assess and compare the knowledge of blood transfusion practices among medical students and residents in Lebanese and Saudi medical institutions. The online survey consisted of 26 questions: 4 about personal data and experience with transfusion and 22 about knowledge on transfusion practices in the areas of blood donation and donor selection, production and storage of blood components, selection of appropriate blood components, administration of blood components, transfusion reactions, and complications. One hundred and twenty-six students from Saudi Arabia, 84 students from Lebanon, 31 residents from Saudi Arabia, and 23 residents from Lebanon participated in the survey. There were no significant differences between students’ and residents’ levels of knowledge. Similarly, there was no difference between the students’ level of knowledge in the two countries. The correct responses (48% and 46%, for students and residents, respectively) were below the acceptable limit of 60% for both groups. This reflects the need for more vigorous and well-structured education and training for both students and residents.